Legal Protection for Consumers Who Suffer Losses Due to Damage to Electronic Goods by Land Expeditions - Bethsaidah Putri Sitorus; Budiman.N.P.D Sinaga; Sovia Febrina Tamaulina Simamora (PT FORMOSA CENDEKIA GLOBAL, 2025)
The legal responsibility of land shipping companies, such as Jalur Nugraha Ekakurir Limited Company, Citra Van Titipan Kilat Limited Company, and Indonesian Post Limited Company, for damage to electronic goods owned by consumers as well as the legal protection available to consumers who suffer losses are the main focus of this study. With the increase in e-commerce transactions, the role of expedition companies is increasingly important in ensuring the safety and integrity of the goods sent. Using a normative legal approach, this study analyzes the applicable norms and regulations, and identifies consumer rights based on Law Number 8 of 1999 on Consumer Protection. The results of the analysis show that expedition companies have an obligation to provide compensation for damages incurred during the delivery process, unless they can prove that the loss was caused by factors beyond their control. In addition, consumers have the right to resolve disputes through non-litigation and litigation channels. The resulting recommendations emphasize the need for increased awareness of expedition companies regarding their legal responsibilities and education for consumers about their rights in e-commerce transactions.